2023
DOI: 10.1038/s42003-023-05026-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of primary and metastatic high-grade serous ovarian cancer tumors reveals distinct features associated with survival

Abstract: High-grade serous ovarian cancer (HGSC) is the most lethal histotype of ovarian cancer and the majority of cases present with metastasis and late-stage disease. Over the last few decades, the overall survival for patients has not significantly improved, and there are limited targeted treatment options. We aimed to better characterize the distinctions between primary and metastatic tumors based on short- or long-term survival. We characterized 39 matched primary and metastatic tumors by whole exome and RNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…We observed a prominent reduction in the proliferation and invasion of OVCAR3CIS cells upon miR-1206 knockdown, and its reduced expression correlates well with ovarian cancer patient outcomes. Our bioinformatic analysis identified more than 20 potential miR-1206 targets, including E2F3 (a transcription factor that regulates cell proliferation) [39] and TP53INP1 (a tumor suppressor gene regulating autophagy) [40]. According to our results, miR-1206 represents an important target for ovarian cancer therapy; therefore, further research is required to identify the miR-1206 targets responsible for the observed biological effects.…”
Section: Discussionmentioning
confidence: 68%
“…We observed a prominent reduction in the proliferation and invasion of OVCAR3CIS cells upon miR-1206 knockdown, and its reduced expression correlates well with ovarian cancer patient outcomes. Our bioinformatic analysis identified more than 20 potential miR-1206 targets, including E2F3 (a transcription factor that regulates cell proliferation) [39] and TP53INP1 (a tumor suppressor gene regulating autophagy) [40]. According to our results, miR-1206 represents an important target for ovarian cancer therapy; therefore, further research is required to identify the miR-1206 targets responsible for the observed biological effects.…”
Section: Discussionmentioning
confidence: 68%
“…While single-cell proteomics methods, such as mass cytometry, can help trace trajectories and rapid and dynamic changes in the TME caused by disease progression or therapies, genetics-based methods contribute to more static TME profiling [46][47][48]. Several studies have applied multiplexing methods to examine the EOC TiME and have reported differing patterns of tumor-infiltrating lymphocytes, as well as associations between CD47 expression on different immune cells and survival parameters, and associations between the distribution of immune cell phenotypes and survival or response to combined therapy with poly-ADP-ribose polymerase and immune checkpoint inhibitors [44,45,49,50]. The present study has also illustrated the identification of a wide array of single-cell phenotypes by mass cytometry-based profiling of the TME, with at least the same level of complexity as other methods; however, the sample size in the present study made the detected clinical associations less reproducible than those reported by Färkkilä et al [44].…”
Section: Discussionmentioning
confidence: 99%
“…PTEN loss has been detected across all HGSOC stages, supporting an early step in the progression of HGSOC [49]. Recently, RB1 mutations were identified exclusively in patients surviving more than 5 years as a marker of long survivorship [50]. Concerning oncogenes, CCNE1, MYC, and MECOM genes have been found amplified in at least 20% of cases [44].…”
Section: Clonal Ith Of Hgsocmentioning
confidence: 95%